Politik Diplomasi Masa Revolusi Menuju Pengakuan Kemerdekaan Indonesia (1946-1949) - edy suparjan; Ibnu Khaldun (LP2M Universitas Sarjanawiyata Tamansiswa, 2021)
This paper aims to find out how the politics of diplomacy in the early days of independence, especially during the Syarir Cabinet to Hatta Cabinet, and to explain how the efforts of the Indonesian political elite to address diplomatic politics in the face of aggression and to analyze the role of third parties in Indonesian diplomacy. The method used in this research is a qualitative method, namely fact finding with the correct interpretation. Descriptive research is to study problems in society and the procedures that apply in society. The method used is literature study with data collection techniques by conducting a review study of books, literature, notes, and reports that have to do with the problem being solved. The conclusion of this research is that the political attitudes of the various Indonesian elites, the first group is that the government prioritizes the political path of diplomacy rather than armed resistance or 100 percent independence. The attitude of this first group is more influenced by the education they have received since studying in the Netherlands, among the first group are; Hatta, Syahrir, Setiadjid, Abdul Majid and Amir Syarifuddin and Agus Salim. This group believes that de jure the Netherlands is still strong and has the support of its allies such as Britain and America. Meanwhile, the second group who chose the armed or guerrilla resistance method in achieving 100 percent independence among this group was more than the opposition and military figures such as Tan Malaka, Panglima Sudirman and the leaders of the Masyumi and PNI parties. This conflict caused Sudirman to choose Guerrilla as the right way to achieve 100 percent independence. The conflict between Indonesia and the Netherlands ultimately requires American involvement in resolving the dispute between the two countries. This was proven by the US for the second time issuing a UN resolution to pressure the Netherlands to want to surrender sovereignty to the Indonesian republic even though under certain conditions, such as the Netherlands has not recognized the states belonging to the Republic of Indonesia and Papua. Then the independence of the Republic of Indonesia still has the remaining debt to the Dutch.Â Keywords : Politics, Diplomacy, Revolution, Independence